2011
DOI: 10.1165/rcmb.2009-0266oc
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Decreases Innate Responses of Epithelial Cells to Rhinovirus Infection

Abstract: Exposure to cigarette smoke is associated with a significant increase in the risk for respiratory viral infections. The airway epithelium is the primary target for both cigarette smoke and respiratory viral infection. We investigated the effects of cigarette smoke on the response of airway epithelial cells to rhinovirus infection. We found that pre-exposure of BEAS-2B cells or primary normal human bronchial epithelial cells (NHBEs) to cigarette smoke extract (CSE) reduced the induction of mRNA of the chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 59 publications
11
58
0
Order By: Relevance
“…Third, RV strains have evolved to evade IFN responses (8). Finally, diminished IFN responses in the airway epithelium are associated with conditions such as asthma and cigarette smoke exposure, in which RV infection results in exacerbated disease (22)(23)(24). Although diverse lines of evidence suggest that virus-induced IFNs contribute to defense against RV infection, increasing evidence from studies in bronchial epithelial cells indicates that the mechanisms involved (i.e., the RLR signaling pathway) require time for up-regulation before mediating a robust IFN response (6,7,9).…”
Section: Discussionmentioning
confidence: 99%
“…Third, RV strains have evolved to evade IFN responses (8). Finally, diminished IFN responses in the airway epithelium are associated with conditions such as asthma and cigarette smoke exposure, in which RV infection results in exacerbated disease (22)(23)(24). Although diverse lines of evidence suggest that virus-induced IFNs contribute to defense against RV infection, increasing evidence from studies in bronchial epithelial cells indicates that the mechanisms involved (i.e., the RLR signaling pathway) require time for up-regulation before mediating a robust IFN response (6,7,9).…”
Section: Discussionmentioning
confidence: 99%
“…Although elevated STAT1 has not been reported in NECs from smokers, STAT1 levels are correlated with COPD diagnosis, and downstream STAT1-dependent genes such as NOS2 are induced in smokers (4,10). Additionally, studies performed in bronchial epithelial cell lines have shown that pretreatment with cigarette smoke extract (CSE) reduces STAT1 activation, whereas other studies report that CSE treatment increased STAT1 activation (13,37).…”
Section: Discussionmentioning
confidence: 99%
“…TLRs play an important role in defense and it can thus be hypothesized that poor TLR function contribute greatly to pulmonary disease exacerbation. Reduced TLR function could cause disease worsening because of comprised sensing of bacterial or viral components (Laan et al, 2004;Kulkarni et al, 2010;Eddleston et al, 2011;Manzel et al, 2011) as well as a reduced ability to phagocytose bacteria (Hodge et al, 2007b;Phipps et al, 2010) and apoptotic cells (Hodge et al, 2003;Richens et al, 2009 …”
Section: A Exacerbation: Causes and Symptomsmentioning
confidence: 99%